COMPENSATION SYSTEM FACTORS INPT. INDONESIANRAILWAYS REGION DIVISION I NORTH SUMATRA - Andriany, Dewi; Arda, Mutia (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
This study aims to see and determine the factors of the Compensation System at PT.Kereta Api Indonesia (Persero) Regional Division I North Sumatra. Theapproachused in this research is an associative approach . The number of samples in this study using the slovin formula was 60 employees. Data collection techniques in this study were using interviews (interviews), documentation studies, and questionnaires (questionnaires). The data analysis technique used is factor analysis technique. Processing data in this study using the SPSS (Statistical Package for the Social Sciences) 16 software program for windows. Through factor analysis obtained which determines the compensation system atPT. Kereta Api Indonesia (Persero) Regional Division I North Sumatra, namely: Factor1 follows the Education Level factor variable. Factor 2 follows the Work Experience factor variable. From the processing of factor analysis, it can be obtained that the most dominant factor determines the compensation system at PT. KeretaApi Indonesia (Persero) Regional Division I North Sumatra is the Education Level factor, where the higher the level of education, the higher the compensation received.